An efficient non-linear GBT-based finite element for steel-concrete beams - Henriques, David (2016)
A computationally efficient GBT based beam finite element is presented, specifically developed for capturing the materially non-linear behaviour of wide flange steel concrete composite beams. The element incorporates shear lag effects, as well as concrete and steel non-linear material behaviour Analytical solutions for elastic shear lag problems are de rived and a set of materially linear and non-linear numerical examples is presented, showing that the proposed beam finite element captures accurately all relevant phenomena with a very small computational cost. For validation and comparison purposes, results obtained with shell/brick finite element models are also presented.